Late onset congenital central hypoventilation syndrome in a child with Down syndrome - Singh, Shweta; Agrawal, Reema (International Journal of Contemporary Pediatrics, 2025)
Congenital central hypoventilation syndrome (CCHS), also known as Ondine syndrome, is a rare genetic disorder characterized by alveolar hypoventilation and dysregulation of the autonomic nervous system. Late onset congenital central hypoventilation syndrome (LOCCHS) has been infrequently reported, particularly in patients with Down syndrome. This case report presents an 8-year-old girl with Down syndrome who developed late onset CCHS. Clinical assessments, laboratory tests, and imaging studies were performed to evaluate her condition. The patient exhibited severe respiratory acidosis and hypoxemia, necessitating intubation and mechanical ventilation. Despite multiple extubation attempts, the patient demonstrated no spontaneous breathing. The diagnosis of LOCCHS was considered after excluding other conditions. Unfortunately, the child expired within 24 hours following extubation. LOCCHS should be contemplated in children with unexplained hypoventilation who are challenging to extubate, particularly in the absence of underlying neurological, pulmonary, or cardiac diseases.